Patients with inflammatory bowel disease have a higher chance of developing periodontitis: A systematic review and meta-analysis - Domokos, Zsuzsanna; Uhrin, Eszter; Szabó, Bence; Czumbel, Márk László; Dembrovszky, Fanni; Kerémi, Beáta; Varga, Gábor; Hegyi, Péter; Hermann, Péter; Németh, Orsolya (Frontiers in Medicine, 2022)
Background and objective: Periodontitis affects up to one billion people worldwide, and has been proven to be associated with several systemic inflammatory conditions. This study investigates the specific relationship between two multifactorial diseases: inflammatory bowel disease (IBD) and periodontitis. To thoroughly explore this issue, we investigated separately whether IBD patients have a higher chance of developing periodontitis, and equally, whether patients with periodontitis have a higher chance of developing IBD. Methods: The systematic search was performed in three databases: MEDLINE, Cochrane Trials, and Embase, up to 26 October 2021. The protocol was registered in PROSPERO. All eligible studies investigating the association between IBD and periodontitis from either direction were included. The Newcastle-Ottawa Scale was used to assess the risk of bias. As a primary outcome, we investigated the prevalence of IBD and periodontitis, and calculated the odds ratio (OR). Our secondary outcomes involved comparing the clinical periodontal outcomes of IBD patients to those of IBD-free patients. Results: The systematic search resulted in 1,715 records, 14 of which were eligible for qualitative synthesis and 8 for quantitative synthesis. On the basis of the results of the primary outcome, IBD diagnosis was associated with significantly higher odds of periodontitis: OR = 2.65 (CI: 2.09 - 3.36, I2=0 (CI: 0 - 0.75)). For subgroup analysis, we investigated separately the odds in Crohn’s disease (CD) patients: OR = 2.22 (CI: 1.49 - 3.31, I2=0.05 (CI: 0 - 0.76)) and in ulcerative colitis (UC) patients: OR = 3.52 (CI: 2.56 to 4.83, I2=0 (CI: 0 - 0.75)); the odds were significantly higher in all cases. Two studies investigated whether patients with periodontitis were more susceptible to IBD, and both found that periodontitis was significantly associated with the risk of subsequent UC, but not with subsequent CD. However, more studies are needed to prove an association. Conclusion: Our analysis confirmed that IBD patients have a higher chance of developing periodontitis, and are a higher risk population in dentistry. Both dentists and gastroenterologists should be aware of this relationship and should emphasize the importance of prevention even more than in the healthy population.